2020
DOI: 10.1111/aos.14447
|View full text |Cite
|
Sign up to set email alerts
|

Increased choroidal thickness: a new indicator for monitoring diabetic macular oedema recurrence

Abstract: Purpose The aim of this study was to determine whether choroidal thickness (CT) increases at the time of exudative recurrence in diabetic patients with unilateral diabetic macular oedema (DME) treated with intravitreal injections of anti‐VEGF or dexamethasone. Methods A real‐life, prospective, two‐centre study was conducted over a 9‐month period investigating diabetic patients presenting with unilateral DME treated with anti‐VEGF or dexamethasone intravitreal injections, and CT was measured manually, using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Conversely, a thick choroid post anti-VEGF may also indicate an eye that is a poor responder to anti-VEGF and an indicator of chronicity of DMO. However, thick choroid is not an indicator for DMO recurrence or higher number of injections [ 89 ]. On the contrary, other investigators have suggested that choroidal blood volume, flow and velocity decreases in diabetic eyes with DMO, which may lead to hypoxia of the outer retina, thereby leading to increase in VEGF levels [ 90 , 91 , 92 ].…”
Section: Objective Factorsmentioning
confidence: 99%
“…Conversely, a thick choroid post anti-VEGF may also indicate an eye that is a poor responder to anti-VEGF and an indicator of chronicity of DMO. However, thick choroid is not an indicator for DMO recurrence or higher number of injections [ 89 ]. On the contrary, other investigators have suggested that choroidal blood volume, flow and velocity decreases in diabetic eyes with DMO, which may lead to hypoxia of the outer retina, thereby leading to increase in VEGF levels [ 90 , 91 , 92 ].…”
Section: Objective Factorsmentioning
confidence: 99%
“…In the work of Mathis et al (2020), there was a relation of CT increase with the anti‐VEGFs' subsiding effect on the choroid, but it was not clear that monitoring CT would be more useful to detect recurrence than monitoring CRT. It is possible that an anti‐VEGFs' waning effect on the choroid does not imply a need for another treatment if the CRT remains stable, that is, changes in CT do not necessarily forecast a DMO recurrence and a need for an additional injection (Mathis et al 2020). Furthermore, it is to be expected that the choroid thickens as the anti‐VEGF effect subsides, because CT decreases as a side effect of anti‐VEGF administration (Campos et al 2018).…”
Section: Figmentioning
confidence: 99%
“…T he choroidal thickness (CT) or the subfoveal choroidal thickness (SFCT) have been indicated as prognostic factors for the treatment of diabetic macular oedema (DMO), including in recent works (Mathis et al 2020;Endo et al 2020). Authors usually engage the decrease in CT and the decrease in central retinal thickness (CRT) under the action of anti-vascular endothelial growth factor (VEGF) agents, in a cause-effect relationship.…”
mentioning
confidence: 99%
“…Whitney U test; SFCT, subfoveal choroidal thickness; SD, standard deviation; μm, micrometer; DME, diabetic macular edema.Journal of Ophthalmology segment-outer segment layer could be OCT biomarkers for better functional success in eyes that received IVD implant injection for DME treatment[20]. In their multicenter and retrospective study, Zur et al reported for the first time in the literature that the IVD implant could ameliorate disorganization of retinal inner layers which is a biomarker in eyes with DME[21].In a prospective study, Mathis et al reported that the increase in choroidal thickness in eyes with DME is an indicator for exudative recurrence that regressed with anti-VEGF or IVD implant injection[22].Kim et al investigated the effect of IVD implant on eyes with DME resistant to anti-VEGF drugs and reported that IVD implant causes an increase in BCVA and a decrease in the central fovea and SFCT thickness [23]. Lee et al reported that IVD implant may cause thinning not only in eyes with DME but also in eyes with retinal vein occlusion…”
mentioning
confidence: 99%